SWOT Analysis of the Implementation of Tax Dispute Administration and Electronic Trials (E-Tax Court) at the Indonesian Tax Court - Prasetyo, Donatius Tri; Rahayu, Ning (Journal Public Policy, 2024)
Implementation of Tax Dispute Administration and Electronic Hearings (E-Tax Court) at the Indonesian Tax Court is an effort to increase the use of technology and information systems in the Indonesian Tax Court process. Implementation E-Tax Court and technology integration can help speed up the process and increase the efficiency of the Indonesian Tax Court. This research aims to analyze implementation E-Tax Court in terms of Analysis Strengths, Weaknesses, Opportunities, And Threat (SWOT) and analyze the supporting factors for successful implementation E-Tax Court in Tax Dispute Administration and Electronic Hearings at the Indonesian Tax Court. This research was conducted using a qualitative approach with a post positivist paradigm. The data collection technique used was through literature study and in-depth interviews. Strength: E-Tax Courtproviding efficiency in terms of time and costs, easy accessibility for users so as to increase transparency and accountability;Weaknesses: E-Tax Court still constrained by technological infrastructure, human resource readiness; Opportunities : application E-Tax Courtis a form of innovation and modernization of the legal system in Indonesia; Threat: e-tax court There are still limited regulations governing implementatione-tax court. Supporting factors for successful implementation E-Tax Court has been noticed by the Indonesian Tax Court. Supporting factors for successful implementation E-Tax Court These include system quality, information quality, service quality, system use, user satisfaction and benefits for users